2020
DOI: 10.1016/j.jvscit.2020.01.006
|View full text |Cite
|
Sign up to set email alerts
|

Management of bilateral renal artery aneurysms with laparoscopic nephrectomy, ex vivo reconstruction, and autotransplantation in a woman planning pregnancy

Abstract: Renal artery aneurysms (RAAs) are rare, with an estimated incidence of 0.01% to 0.97%. These aneurysms are often asymptomatic, although they occasionally manifest with hypertension, back pain, hematuria, or rupture. Despite limited evidence guiding treatment, women of childbearing age are consistently offered treatment because of the high risk of rupture. We present a case of a woman planning pregnancy with bilateral RAAs after failed endovascular management. She underwent bilateral laparoscopic nephrectomy, e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 7 publications
0
2
0
Order By: Relevance
“…One study noted an increased risk of renal infarction with endovascular management (22%) compared with open reconstruction (5%). 7 Open surgical repair is more common for RAAs with more efferent branches. 4 …”
Section: Discussionmentioning
confidence: 99%
“…One study noted an increased risk of renal infarction with endovascular management (22%) compared with open reconstruction (5%). 7 Open surgical repair is more common for RAAs with more efferent branches. 4 …”
Section: Discussionmentioning
confidence: 99%
“…In most studies, the use of laparoscopy is limited and mostly applied for nephrectomy ( Hiess and Seitz, 2016 ; Siena et al, 2019 ; Kishore et al, 2020 ). After nephrectomy, renal vessels are extracted from the abdominal cavity and transferred to the bench table, and a separate incision is required to anastomose the renal vessels with the iliac vessels ( Kubota et al, 2020 ; Pomy et al, 2020 ; Smith et al, 2020 ). Although some studies have reported intracorporeal robot-assisted renal autotransplantation and restrictions due to kidney cold preservation in vivo , the kidney is not cold preserved continuously during the operation after vessel dissociation ( Breda et al, 2021 ).…”
Section: Introductionmentioning
confidence: 99%